2018
DOI: 10.1542/peds.2017-1076
|View full text |Cite|
|
Sign up to set email alerts
|

A Home Visiting Parenting Program and Child Obesity: A Randomized Trial

Abstract: Using the MTB program, we significantly lowered the rate of obesity among 2-year-old children living in low-socioeconomic-status communities. In addition, children of Hispanic mothers were less likely to have overweight or obesity at 2 years. Given the high and disproportionate national prevalence of Hispanic young children with overweight and obesity and the increased costs of obesity-related morbidities, these findings have important clinical, research, and policy implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…A recent systematic review of interventions in the first 2 years of life found nine interventions that improved weight status in young children . While no one type of intervention setting or program was most successful, individualized interventions in the home and interventions that focused on changing behaviours at the family level were most often effective . ECHO used an existing home visitation program and focused on multiple infant feeding behaviours, sleep and TV/screen time, in addition to maternal diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of interventions in the first 2 years of life found nine interventions that improved weight status in young children . While no one type of intervention setting or program was most successful, individualized interventions in the home and interventions that focused on changing behaviours at the family level were most often effective . ECHO used an existing home visitation program and focused on multiple infant feeding behaviours, sleep and TV/screen time, in addition to maternal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity prevention is not part of the PAT curriculum although educational handouts related to topics such as breastfeeding and infant sleep are supplemental materials in the PAT curriculum. Two recent publications suggest that obesity prevention messages can be incorporated into home visitation programs and may successfully prevent/reduce obesity in mothers and their infants …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive statistics [ 34 ], Analysis of Variance (ANOVA) [ 35 , 36 ], neural networks [ 37 ], regression [ 38 , 39 , 40 , 41 , 42 ] and fuzzy sets [ 43 ] are popular statistical methods of analyzing obesity. Among these statistical modeling techniques, regression (bivariate or multivariate) is the most widely used to analyze child obesity modeling.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, we need effective prevention strategies that address the contextual and behavioral factors contributing to obesity in low‐income and minority groups. To date, some have shown efficacy , and those that used home visits and addressed parenting styles have shown success , including one targeting low‐income Hispanic families . Investment in developing successful programs is needed to reduce health inequities and ensure the well‐being of all our children.…”
mentioning
confidence: 99%